Decrease in in vivo coagulant potential of emicizumab in a patient with hemophilia A and inhibitor complicated with infectious mononucleosis. Issue 2 (7th March 2023) - Furukawa, Shoko; Ogiwara, Kenichi; Yada, Koji; Takeyama, Masahiro; Niino, Tomomi; Shima, Midori; Keiji, Nogami
Abstract : Emicizumab prophylaxis significantly reduces bleeding episodes in patients with hemophilia A (PwHA). There is little information on coagulant potentials in emicizumab-treated PwHA with infection, however. We encountered an emicizumab-treated PwHA with inhibitor, complicated with Epstein–Barr virus-associated infectious mononucleosis (IM) in phase 1/2 study (ACE001JP/ACE002JP). Although it was a typical clinical course of IM, activated partial thromboplastin time was mildly prolonged but rotational thromboelastometry revealed severely impaired coagulant potential. The blood concentration of emicizumab decreased moderately in the low concentration range, resulting in an increased risk of bleeding and possibly leading to severe ileocecal bleeds requiring coil embolization. The blood concentrations of factors IX/X little decreased and antiemicizumab antibodies did not develop, however. After the influence by IM resolved, his coagulant potentials gradually recovered with the recovery of emicizumab concentration, and parameters by global coagulation assays improved. An IM case for emicizumab-treated PwHA may need to monitor using global coagulation assays.